FAO research and technology paper N.7 - A Zaid (FAO, 1999)
This book brings up to date the terms more frequently used by writers and workers on modern biotechology and genetic engineering. It includes terms used in genetics, biochemistry, physiology, tissue culture, immunology and animal reproduction.